Determinants of Development Inequality Between Regions in North Sumatra Province - Harahap, Darwis; Matondang, Zulaika; Harahap, Susanti; Farizal, Nando (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
The area to be built must be evenly distributed in Indonesia, uneven development causes jealousy and dissatisfaction between regions. based on this will be detrimental to the development that a region wants to achieve. The formulation of the problem in this study is whether there is an influence of economic growth in population and the human development index on development inequality in the province of North Sumatra. The type of research used in this research is quantitative research. The results of the study indicate that the economic growth of the population has an effect on development inequality. While the human development index has no effect on development inequality.